The rich get richer and the poor get poorer: Social media and the post-IPO behavior of investors in biotechnology firms. The relationship with Twitter volume - Smadar Siev (Journal of Risk and Financial Management, 2021)
This paper analyzes stock returns for biotechnology firms after initial public offering (IPO) and explores the effect of social media-specifically, Twitter-on these returns. The results indicate positive yet insignificant cumulative average abnormal returns (CAARs) of 1.97% in the first 25 days post-IPO and a decline of tens of percentage points over the following three years. However, after dividing the sample firms into two subsamples according to size, either under or over USD 500 million in market value, the overall results change dramatically. Firms with a market value lower than USD 500 million yield negative CAARs immediately following the IPO; however, this negative CAAR becomes significant only from day 50 onward. Firms with a market value over USD 500 million yield positive CAARs immediately following the IPO, which become significant from day 50, remaining so throughout the following year. These findings can be attributed to the limited duration of investors' attention, which increases until the end of quiet period and, with small-sized firms, diminishes during the post-IPO years. An examination of Twitter activity and share returns demonstrates a robust correlation between the two, suggesting that investors' attention to firms may be reflected in their Twitter usage.
Keywords: D8; G11; G14; G17; 330; behavioral finance; biotechnology companies; financial markets; IPO; Twitter